An Exploration on Ethnic Group Courses - from the Indigenous’ Cultural Value System in Taiwan - Lin, Shu Chi (Technium Social Sciences Journal, 2021)
Articles 14 and 15 of the United Nations Declaration on the Rights of Indigenous Peoples assert that indigenous peoples have the right to establish and control their educational systems and institutions in their own languages and in a manner appropriate to their cultural methods of teaching and learning, in order that their cultures, traditions and histories may be appropriately reflected in education. States should take effective measures, in conjunction with indigenous peoples, to provide indigenous students with the opportunity to receive education in their own language and about their own culture. The study of Taiwan's indigenous culture is a unique representation of each ethnic group's culture, and to meet the needs of social development, ethnic issues should be promoted in education. The ideal curriculum, as mentioned by Tye (1979), has to be transformed into a formal curriculum by incorporating it into the national syllabus, and then into a practical operational and experiential curriculum through the perceptual curriculum understood by teachers. In other words, the content of national education (including the three levels of national concept, national system and national material) must be transformed in the "curriculum-determining levels" of ideal, formal, perception, operation and experience. In Taiwan, there are four major ethnic groups, including the provincial, Minnan, Hakka, and aboriginal peoples, which have a very diverse and complex culture. However, the process of transforming indigenous cultures from understanding to practice has caused many confusions among teachers, which has become a key issue in the development of ethnic curriculum. The past curriculum has a more mainstream cultural established curriculum nature, but the multicultural promotion of ethnic characteristics has a sprouting and teaching revitalization orientation, which makes the original "mainstream established curriculum" and "characteristic ethnic curriculum" incompatible with each other stand out, resulting in a kind of reconciliation demand. Therefore, this study mainly investigates the life and curriculum landscape that emerges from the knowledge of indigenous peoples and their cultural value system, and further interprets the meaning of the curriculum behind it. It also analyzes the connotations of cultural value system response teaching and explores the development and application strategies of ethnic-specific curricula.